2021
DOI: 10.1080/15384047.2021.1899573
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a rare GKAP1-NTRK2 fusion in a pediatric low-grade glioma, leading to targeted treatment with TRK-inhibitor larotrectinib

Abstract: Here we report a case of an 11-year-old girl with an inoperable tumor in the optic chiasm/hypothalamus, who experienced several tumor progressions despite three lines of chemotherapy treatment. Routine clinical examination classified the tumor as a BRAF -negative pilocytic astrocytoma. Copy-number variation profiling of fresh frozen tumor material identified two duplications in 9q21.32–33 leading to breakpoints within the GKAP1 and NTRK2 gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…ROS fusions are emerging as clinically important since they can be targeted by small inhibitors. Hence, it is becoming crucial to identify ROS-driven tumors by genetic screening so that the patients may benefit from these treatments (5,14,47,(60)(61)(62)(63). Several ROS inhibitors that have been developed are mainly tested for adult patients with NSCLC (64).…”
Section: Discussionmentioning
confidence: 99%
“…ROS fusions are emerging as clinically important since they can be targeted by small inhibitors. Hence, it is becoming crucial to identify ROS-driven tumors by genetic screening so that the patients may benefit from these treatments (5,14,47,(60)(61)(62)(63). Several ROS inhibitors that have been developed are mainly tested for adult patients with NSCLC (64).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, whether TrkB fusion exists in MPNSTs needs further discussion in the future. To alleviate these abnormalities, several small-molecule compounds targeting TRK fusions have been developed and tested in preclinical and clinical trials, and they have shown remarkable antitumour activities in different cancers, including different neurogenic neoplasms [ 63 , 64 ]. This study firstly suggests that further developing inhibitors targeting BDNF/TrkB signalling has great application prospects in the treatment of NF1-derived MPNSTs.…”
Section: Discussionmentioning
confidence: 99%
“…The neurotrophic receptor of tyrosine kinase (NTRK) family and the ALK gene have significant roles in the development and fuctions of the CNS (81-88). In pLGGs, NTRK gene fusions including NTRK1/2/3, SLMAP-NTRK2, TPM3-NTRK1, RBPMS-NTRK3 and ETV6-NTRK3 are rare (64,76,121,122). ALK alterations are also uncommon in pLGGs, but the fusions that involved CCDC88A and PPP1CB with AKT being the more prevalent and resulting from chromothripsis (123)(124)(125).…”
Section: Other Alterations In Plggs and Targeted Therapymentioning
confidence: 99%